Regulation of monocyte/macrophage polarisation by extracellular RNA - Cabrera-Fuentes, Hector A.; Lopez, Mercedes L.; McCurdy, Sara; Fischer, Silvia; Meiler, Svenja; Baumer, Yvonne; Galuska, Sebastian P.; Preissner, Klaus T.; Boisvert, William A. (Thrombosis and Haemostasis, 2015)
Monocytes/macrophages respond to external stimuli with rapid changes in the expression of numerous inflammation-related genes to undergo polarisation towards the M1 (pro-inflammatory) or M2 (antiinflammatory) phenotype. We have previously shown that, independently of Toll-like receptor activation, extracellular RNA (eRNA) could exert prothrombotic and pro-inflammatory properties in the cardiovascular system to provoke cytokine mobilisation. Here, mouse bone marrow-derived-macrophages (BMDM) differentiated with mouse macrophage-colony-stimulating factor (M-CSF) were found to be skewed towards the M1 phenotype when exposed to eRNA. This resulted in up-regulated expression of inflammatory markers such as Tnf-α and Il-6, together with Il-12 and iNOS, whereas anti-inflammatory genes such as chitinase-like proteins (Ym1/2) and macrophage mannose receptor-2 (Cd206) were significantly down-regulated. Human peripheral blood monocytes were treated with eRNA and analysed by micro-array analysis of the whole human genome, revealing an up-regulation of 79 genes by at least four-fold; 27 of which are related to signal transduction and 15 genes associated with inflammatory response. In accordance with the proposed actions of eRNA as a pro-inflammatory “alarm signal”, these data shed light on the role of eRNA in the context of chronic inflammatory diseases such as atherosclerosis.
Keywords: Extracellular RNA; inflammation; microarray technology; gene expression; monocyte/macrophage polarisation